Loot box consumption by adolescents pre- and post- pandemic lockdown - Whitney DeCamp; Kevin Daly (PeerJ, 2023)
Loot boxes are virtual items that can be redeemed to receive randomly selected other virtual items, and have been criticized for being similar to gambling. The presence of loot boxes in video games has dramatically increased since 2010, with little evidence available for the current prevalence rate of loot box purchasing in the general population, particularly during and following the COVID-19 pandemic lockdowns. This study uses data from representative samples of American youth to estimate prevalence rates for video game play and loot box consumption before the pandemic (2019) and after the pandemic lockdowns (2022) to examine whether the pandemic has affected loot box usage in the general population and among gamers. The results suggest that youth loot box consumption has increased, rising from 24.9% in 2019 to 31.6% in 2022 among 8th grade (age 13–14) youth. The increase over this time period was larger for girls, though boys are still more likely to purchase loot boxes overall.